A ordem preferencial de beneficiários das terras destinadas à reforma agrária: uma análise à luz da teoria do direito de Ronald Dworkin - Tayer Neto, Pedro Felippe (2014)
The article 19 of Law n. 8.629/93 dispose about the National Agricultural Land Reform Program beneficiaries’ list, without, however, establishing how the lists should be prepared. Currently, the Federal Special Prosecutor at the National Institute of Colonization and Agraricultural Land Reform (PFE/INCRA) believes that it is a legislation’s gap, leaving up to her discretion the list’s draw. The purpose of this paper is to demonstrate how the argument does not hold, based on Ronald Dworkin’s Law theory. As a social institution of political nature, Law’s correct interpretation should be that which best describes the social practices within an idea of integrity, and, in Brazil, the agrarian reform policy exists to mitigate the conservative modernization’s pernicious consequences. In the first chapter will be exposed Brazil’s agricultural land reform’s historical demand, as well as the transformations that the Brazilian’s agricultural process suffered during the twentieth century, since Law cannot be understood outside its historical context. In the second chapter the Union's position will be legally considered according to Dworkin's theory of law. It is proposed a qualitative approach on the subject’s avaliable literature.